TAHLIĪL TADARRUJ AL-MAWĀD AN- NAHWIYYAH FĪ KITĀBAY MULAKHAS QAWĀ’ID AL-LUGAH AL-‘ARABIYYAH WA JĀMI’ AL-DURŪS AL-‘ARABIYYAH (DIRĀSAH MUQĀRANAH) - Ramadhani, Ahmad (STIQ Amuntai, 2022)
This study aimed to determine the gradation system used to organize the material in the book Mulakhkhash Qawa'id Al-Lughah Al-'Arabiyyah and Jami' Ad-Durus Al-'Arabiyyah. This research is included in the type of library research using a qualitative approach. This paper relies on bibliographic sources in the form of books and articles in scientific journals related to the subject matter. The collected data will be analyzed critically and in-depth through data triangulation, data reduction, data presentation and conclusion drawing. The Mulakhkhash book is based on linguistic categories using grammatical gradations. As for the gradation factor, this book pays attention to the factors of learning objectives and the level of students' abilities. This book is intended for students at all levels. While the book Jami 'Ad-Durus uses straight gradations based on linguistic categories using grammatical gradations. As for the gradation factor, this book pays attention to the learning objectives and level of students' abilities. This book is intended for students at the upper level. These two books can be categorized as good Arabic textbooks in terms of material gradation.